Novel electrochemical reactions related to electrodeposition and electrochemical synthesis - Ito Y.; Nishikiori T. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Novel electrochemical reactions in molten salts related to electrodeposition and electrochemical synthesis are reviewed to show their usefulness and possibilities in producing functional materials. Surface nitriding of various metals and stainless steels is possible by the use of anodic reaction of nitride ion (N3-) in LiCl-KCl-Li3N melts. Electrochemical hydrogen absorption/desorption reaction occurs in molten salts containing hydride ion (H-). Electrochemical implantation and displantation can be applied to form transition metal-rare earth metal alloys in LiCl-KCl melts containing rare earth chlorides. As non-conventional electrochemical reactions, direct electrochemical reduction of SiO2 to Si, discharge electrolysis to form metal oxide particles and electrochemical plantation of Zr on ceramics are described.